Light Gage Steel Infill Panels in Multistory Steel Frames - Miller, Craig J. (Engineering Journal, 1974)
In the design of multistory structures, providing adequate lateral stiffness is often more difficult than satisfying strength requirements. For steel structures of 20 or more stories, deep or heavy beams are often required to maintain drift within acceptable limits. In many structures, vertical trusses, concrete shear walls, or a combination of these and rigid frames are used to achieve the required displacements. For very tall structures, various types of tube construction are often used. The price paid for achieving stiffness in these ways is a decrease in the ductility of the structure, with important effects on its behavior under earthquake loading. The reason for this is that the increased total lateral base shear, required for stiffer systems by the Uniform Building Code, sometimes results in a change to a less ductile system. It is desirable to achieve an increase in stiffness without paying the penalty in decreased ductility. One attempt to do this is the slit concrete panel construction which the Japanese have developed. Normally, the strength and stiffness of infilling elements such as interior and exterior partitions are ignored in designing multistory frames, although such elements are acknowledged to make a substantial contribution to the lateral stiffness of the structure. A research program sponsored by the Committee of Structural Steel Producers and the Committee of Steel Plate Producers of the American Iron and Steel Institute was begun at Cornell University to assess the suitability of light gage steel infill panels for providing additional stiffness in multistory structures. The first portion of the research focused on developing the capability to analyze the infill-frame combination, making use of the finite element displacement method of analysis. The second portion, which is currently in progress, is an attempt to verify the analytical results experimentally and to assess the behavior of the panel-frame combinations at loads for which elastic analysis is not valid.